2017
DOI: 10.5194/isprs-archives-xlii-5-w1-647-2017
|View full text |Cite
|
Sign up to set email alerts
|

Virtual in Real. Interactive Solutions for Learning and Communication In the National Archaeological Museum of Marche

Abstract: ABSTRACT:Today the ICTs are favourable additions to museum exhibitions. This work aims to realize an innovative system of digital exploitation of artefacts in the National Archaeological Museum of Marche (MANaM), in order to create a shared museum that will improve the knowledge of cultural contents through the paradigm "learning by interacting" and "edutainment".The main novelty is the implementation of stand-alone multimedia installations for digital artefacts that combine real and virtual scenarios in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…A literature review was conducted focused on multisensory applications in CH, with VR and/or AR, among the last decades. Most common multisensory applications are indoor and based on VR [19], [25]- [27], but some interesting AR installations alluding to multisensory experiences are found, such as the "Multisensory Art Gallery", at the Tate Britain art gallery in London, United Kingdom [28], the "Refugi 307" bomb shelter, from the Spanish Civil War [29], and the mobile multisensory AR project M5SAR in Faro, Portugal [30].…”
Section: A Multisensory Systems In Chmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review was conducted focused on multisensory applications in CH, with VR and/or AR, among the last decades. Most common multisensory applications are indoor and based on VR [19], [25]- [27], but some interesting AR installations alluding to multisensory experiences are found, such as the "Multisensory Art Gallery", at the Tate Britain art gallery in London, United Kingdom [28], the "Refugi 307" bomb shelter, from the Spanish Civil War [29], and the mobile multisensory AR project M5SAR in Faro, Portugal [30].…”
Section: A Multisensory Systems In Chmentioning
confidence: 99%
“…While analysing previous work, it was observed that, when evaluating multisensory systems, the literature provides results mainly obtained in environments relatively controlled by selecting participants or by being tested with expert users [13]- [16], [18], [19]. As mentioned in a previous survey regarding virtual museums [20], we reinforce the need for more evaluation studies involving end-users in order to better understand further implementations, especially, considering that typical users of these technological conditions among CH are non-experienced and non-trained people, who aim to find meaningful and pleasant experiences in a very limited amount of time, precluding them from having slow learning curves [21].…”
mentioning
confidence: 99%
“…While audiovisual approaches appear to be the most commonly used solutions in previous implementations and studies, multisensory approaches have arisen and indicated to further enrich users' experience in cultural heritage (CH) contexts [2], [3]. The recent literature has presented several multisensory strategies using virtual and augmented reality technologies for different types of heritage sites, such as the "Haptic Museum" [4], the "Museum of Pure-Form" [5], the "National Archaeological Museum of Marche" [6], "The Feelies" [7], or the "Tanning in Medieval Coventry" [8]. Some approaches are targeted explicitly for AR technologies, such as the "Zelige Door on Golborne Road" [9], the "M5SAR" [10], and the two case studies of AR multisensory approaches in CH exhibitions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evaluations have frequently been limited to user tests carried out in controlled environments with preselected participants instead of end-users (e.g. [6], [14], [17], [38]), a fact also highlighted by [34]. In addition, few explorations have been made using AR as visual technology instead of VR across multisensory implementations, even if the literature presents AR as a technology that can be preferable when compared to some virtual reality solutions [39].…”
Section: Introductionmentioning
confidence: 99%
“…Information and Communication Technology (ICT) are rapidly developing allowing the real-time management of high resolution reality based models giving the possibility to create an alternative immersive reality that replaces the real world (Boas, 2013). The importance of using ICT in order to make culture accessible to a wider audience is demonstrated in (Clini et al, 2017) and in particular IVR digitally could provide an experience of the caves in a non-destructive way of visiting without damaging, dirtying or altering the site (Jiménez Fernández-Palacios et al, 2017).…”
Section: Related Workmentioning
confidence: 99%